ANALISIS PERBANDINGAN METODE EOQ DAN METODE POQ DENGANMETODE MIN-MAX DALAM PENGENDALIAN PERSEDIAAN BAHAN BAKU PADA PT SIDOMUNCUL PUPUK NUSANTARA - Careza - Rizky; Yuli - Sudarso; Sri Eka Sadriatwati (Politeknik Negeri Semarang, 2016)
Inventory control of raw materials is veryimportant in proses production in thecompany, without inventory control, thecompany will face the risk that the companycannot production goods and fulfill thecustomer demand on time.PT Sidomuncul Pupuk Nusantaraimplemented the Min-Max method in theirinventory control of Biolit but in the actualthis method does not fit properly. They ordersraw materials still available by aconsiderable amount in the warehouse andwith quantity between 100-300kg per orders,there is over stock.EOQ method and POQ method could solvethat problem, they could determine the orderquantity become more economical, minimizereorder cost, and storage costs. Inventorycontrol will be optimal if PT SidomunculPupuk Nusantara used EOQmethod becausethe company does not require warehouse withgreat capacity for saving their quantity,thecarrying cost for biolit will be less,depreciation can also be reduced, theinsurance cost will be less. Frequency ofpurchases for EOQ method as much as 42times a year with quantity of 26 kg per orders.EOQ method can save the inventory cost ofraw materials as much as Rp127.985.727,-from Rp 182.053.200 (actual state of thecompany) to be Rp54.067.473 (EOQ Method)